2019
DOI: 10.3390/polym11010144
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Glycerol Oligomers with Two New Types of End Groups in the Presence of a Homogeneous Alkaline Catalyst

Abstract: The purpose of this work was to synthesize and characterize oligoglycerols with the chains of more than four repeating units. Those oligoglycerols may have some interesting applications, among others, as polyoxyalkylation starters. The glycerol oligomerization process was carried out during 12 h, at 230 °C, under the pressure of 0.4 bar, with the use of sodium carbonate as a homogeneous basic catalyst; various concentrations of the catalyst in the reaction medium were used. The reaction products were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In contrast, alkaline homogeneous catalysts, such as hydroxides, carbonates, or oxides of alkali metals, lead to products of various structures [ 5 ]. Our previous studies showed that, as a result of glycerin oligomerization carried out with the use of sodium carbonate as a basic homogeneous catalyst, it is possible to obtain a mixture of linear oligoglycerols with an average molecular weight exceeding even 400 g/mol containing an additional hydroxyl group at the α carbon atom [ 12 ]. The disadvantages of homogeneous catalysts, however, include their insufficient thermal stability and difficulties with their isolation from the post-reaction mixture, and at the same time they often cause corrosion of the equipment and generate the need to process a large amount of liquid waste.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, alkaline homogeneous catalysts, such as hydroxides, carbonates, or oxides of alkali metals, lead to products of various structures [ 5 ]. Our previous studies showed that, as a result of glycerin oligomerization carried out with the use of sodium carbonate as a basic homogeneous catalyst, it is possible to obtain a mixture of linear oligoglycerols with an average molecular weight exceeding even 400 g/mol containing an additional hydroxyl group at the α carbon atom [ 12 ]. The disadvantages of homogeneous catalysts, however, include their insufficient thermal stability and difficulties with their isolation from the post-reaction mixture, and at the same time they often cause corrosion of the equipment and generate the need to process a large amount of liquid waste.…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical modifications obtained by oxidation, hydrogenolysis, etherification, esterification, dehydration and oligomerisation of glycerol have led to the production of various value-added chemicals. These glycerol derivatives have specific applications in the polymer, agrochemical and pharmaceutical industries [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical transformation processes have been used for glycerol to improve its commercial availability and biodiesel economics. These processes are known as carboxylation [3], hydrogenolysis [4,5], selective oxidation [6], dehydration [7], oligomerization [8], etherification [9] and esterification or acetylation [10].…”
Section: Introductionmentioning
confidence: 99%